Penerapan Software SAP2000 pada Re-Design Struktur Gedung Terpadu Psikologi Olahraga Universitas Negeri Surabaya - Fajar Muhamad Nabil; Muhammad Ramadhan Tegar Bagaskoro; Asri Nurdiana; Bambang Setiabudi (Universitas Diponegoro, 2023)
Building structure planning has an important role for further consideration before the implementation of construction in the field to anticipate construction failure, so it requires knowledge based on applicable rules and strengthened with software to support construction success. The structural planning research on the re-design of the UNESA Sports Psychology Integrated Building project using SAP2000, aims to provide knowledge in applying the concept of building structure design and has an output in the form of structural dimensions and reinforcement in accordance with the rules of PPIUG 1983, SNI 1726-2019, SNI 1727-2020, SNI 2847-2019, and RSA Ciptakarya. The method used is planning the dimensions of the upper structure, analyzing the working load, analyzing the structure using SAP2000, and planning the lower structure with a strong bearing capacity to accept the vertical load of the structure from the SAP2000 analysis results. Based on the final results obtained for the floor slab has two types S1 (12 cm thick, Ø10- 150), S2 (10 cm thick, Ø10-150), Tiebeam and beams with types TB1 (40/75 cm 6D22), B1 (50/70 cm 13D22), B1a (50/70 cm 11D22), B2 (40/60 cm 9D19), B3 (30/50 cm 9D19), B4 (30/40 cm 8D19), Columns of type K1 (80/80 cm 22D22), K1a (80/80 cm 24D22), K1b (80/80 cm 20D22), K1c (80/80 cm 18D22), K2 (70/70 cm 18D22), K3 (68/68 cm 16D22), K4 (60/60 cm 16D19), KL (43/43 cm 10D19), and foundations with a spoonpile diameter of 60 cm number 4 with pilecap dimensions (350/350 cm D16-150).